2022
DOI: 10.1128/jvi.01486-21
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpesvirus 1 Invasion of Sensory Neurons by Retrograde Axonal Transport Is Dependent on the pUL37 Region 2 Effector

Abstract: A molecular and cellular understanding of the retrograde axonal transport process that underlies the neuroinvasive properties of the alphaherpesviruses is established from studies of herpes simplex virus and pseudorabies virus. The degree to which this phenotype is conserved in other related viruses has largely not been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…His team showed that the kinesin used for the latter step is not recruited from the cytoplasm during transport, but rather is incorporated and assimilated into the viral particle in a previously infected cell [ 21 ]. In his talk, he will also explain how a viral effector protein spatially and temporally regulates the assimilated kinesin motor to promote rapid intracellular trafficking of capsids to the nucleus, switching from long-distance dynein-driven transport [ 22 ].…”
mentioning
confidence: 99%
“…His team showed that the kinesin used for the latter step is not recruited from the cytoplasm during transport, but rather is incorporated and assimilated into the viral particle in a previously infected cell [ 21 ]. In his talk, he will also explain how a viral effector protein spatially and temporally regulates the assimilated kinesin motor to promote rapid intracellular trafficking of capsids to the nucleus, switching from long-distance dynein-driven transport [ 22 ].…”
mentioning
confidence: 99%